Effects of dietary substitution of fishmeal by black soldier fly (Hermetia illucens) meal on growth performance, whole-body chemical composition, and fatty acid profile of Pontastacus leptodactylus juveniles - Alvanou, Maria V.; Kyriakoudi, Anastasia; Makri, Vasiliki; Lattos, Athanasios; Feidantsis, Konstantinos; Papadopoulos, Dimitrios K.; Georgoulis, Ioannis; Apostolidis, Apostolos P.; Michaelidis, Basile; Mourtzinos, Ioannis; Asimaki, Adamantia; Karapanagiotidis, Ioannis T.; et al. (Frontiers in Physiology, 2023)
Freshwater crayfish are considered aquatic products of high quality and nutritional value. The increasing demand led to populations reduction in several locations throughout their range. Thus, the development of appropriate rearing conditions is considered necessary, among which, optimization of their diet is basic. In the present study, a 98-day feeding trial was carried out to evaluate the impact of dietary fishmeal substitution by Hermetia illucens meal on Pontastacus leptodactylus juveniles kept under laboratory conditions. Insect meals represent an environmentally friendly solution, considered as a high-value feed source, rich in nutrients such as protein and fat. Three dietary regimens were utilized with a fishmeal-based without Hermetia meal (HM) defined as the control diet (HM0), and two diets, the first with 50% (HM50) and the second with 100% (HM100) of fishmeal substitution by HM, respectively. Growth performance, whole-body composition, and fatty acid profiles of individuals were studied in the different treatments. At the end of the feeding trial, statistically significant differences were observed in the mean survival rate (SR), specific growth rate (SGR), feed conversion ratio (FCR) and weight gain (WG). Specifically, animals fed with HM-based diets had higher mean SR, while the control group performed better regarding FCR and SGR. The HM inclusion in the diet significantly altered the whole-body chemical composition of the crayfish signifying a different metabolic utilization compared to fishmeal (FM). The fatty acid analysis revealed that 16:0 (palmitic acid) was the predominant saturated fatty acid (SFA), 18:1ω9 (oleic acid) was found to be the main monounsaturated fatty acid (MUFA), while 18:2ω6 (linoleic acid) represented the major polyunsaturated fatty acid (PUFA) followed by C20:3 cis ω3 (cis-11-14-17-eicosatrienoate) and C22:6 cis ω3 (cis-4,7,10,13,16,19-Docosahexaenoic) fatty acids. The inclusion of dietary HM significantly reduced the contents of ∑SFAs, ∑PUFAs and ∑ω6 fatty acids, as well as those of C22:6 cis ω3 and increased the ω6/ω3 and hypocholesterolemic to hypercholesterolemic ratios in the body. In parallel with improvements in balanced diets and in culture conditions that need to be optimised for rearing of freshwater crayfish, our study provides new data that enlighten the suitability of insect meals in nutrition of P. leptodactylus.